2010
DOI: 10.1186/1471-244x-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Standards of lithium monitoring in mental health trusts in the UK

Abstract: BackgroundLithium is a commonly prescribed drug with a narrow therapeutic index, and recognised adverse effects on the kidneys and thyroid. Clinical guidelines for the management of bipolar affective disorder published by The National Institute for Health and Clinical Excellence (NICE) recommend checks of renal and thyroid function before lithium is prescribed. They further recommend that all patients who are prescribed lithium should have their renal and thyroid function checked every six months, and their se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 23 publications
2
91
1
Order By: Relevance
“…Since Li is not bound to serum proteins, it is freely filtered by the kidneys and its elimination depends on the glomerular filtration rate. Consequently, Li blood levels and undesirable effects caused by Li are directly related to renal function (9,10). The participants of this study were assessed by measurements of blood urea and creatinine, which were within normal limits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Li is not bound to serum proteins, it is freely filtered by the kidneys and its elimination depends on the glomerular filtration rate. Consequently, Li blood levels and undesirable effects caused by Li are directly related to renal function (9,10). The participants of this study were assessed by measurements of blood urea and creatinine, which were within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to a classic PHP and even to a normocalcemic HPT or hypercalcemia without PTH elevation (9,26,27). Both in vitro studies and in vivo studies in healthy volunteers demonstrated direct action of lithium on parathyroid cells in releasing intact PTH (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 95% of the ingested dose is excreted in the urine without undergoing biotransformation. Its half-life is up to 24 hours and may be longer in the elderly (1,3). Approximately 80% of lithium is reabsorbed in the proximal renal tubules.…”
Section: Pharmacological Aspectsmentioning
confidence: 99%
“…Currently, they are available in immediate-and extended-release formulas and are used to treat mania, refractory and recurrent depression and bipolar disorders with reduced morbidity and mortality. Despite recent advances in pharmacological treatment of psychiatric disorders, these salts remain effective and inexpensive alternatives (3,4).…”
Section: Introductionmentioning
confidence: 99%